1974
DOI: 10.1115/1.3450189
|View full text |Cite
|
Sign up to set email alerts
|

Local and Average Transfer Coefficients for One-Row Plate Fin and Tube Heat Exchanger Configurations

Abstract: The analogy between heat and mass transfer has been used to obtain local and average transfer coefficients for a one-row plate fin and tube heat exchanger configuration. The mass transfer experiments were performed using the naphthalene sublimation technique. A heat exchanger passage was modeled using naphthalene plates; spacer disks simulated the tubes. Detailed measurements of the surface elevation of the naphthalene plates were made before and after a data run, and this enabled evaluation of the local trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 0 publications
0
31
0
2
Order By: Relevance
“…Then, Schulemberg [2] conducted similar study for plate fin and elliptic tubes. Saboya and Sparrow [3][4][5] used the naphthalene sublimation technique in order to obtain local and overall heat and mass transfer coefficients for different configurations, experimentally. Webb [6] reported that elliptical tubes have better performance than circular tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Schulemberg [2] conducted similar study for plate fin and elliptic tubes. Saboya and Sparrow [3][4][5] used the naphthalene sublimation technique in order to obtain local and overall heat and mass transfer coefficients for different configurations, experimentally. Webb [6] reported that elliptical tubes have better performance than circular tubes.…”
Section: Introductionmentioning
confidence: 99%
“…평판 핀 열교환기의 경우 핀 선단으로 부터의 경계층과 원관 주위의 말굽 와류가 중 요한 열전달 메카니즘으로 알려져 있다 [4]. 웨이브 핀 열 교환기의 중요한 전열 촉진 메카니즘은 유동 혼합과 골 부근에서 형성되는 Goetler 와류로 알려져 있다 [5,6] …”
Section: 서론unclassified
“…By measuring the napthalene profile on the test surface before and after the experiment has been performed, local mass transfer coefficients may be determined. This technique has been used to study forced convection in a one-row plate fin and tube heat exchanger [44].…”
Section: Background and Previous Workmentioning
confidence: 99%